An Analysis of the Theories and Explanations Offered for the Mispricing of Accruals and Accrual Components - KRAFT, ARTHUR; LEONE, ANDREW J.; WASLEY, CHARLES (Journal of Accounting Research, 2006)
ABSTRACT Numerous accounting studies claim that investors fail to rationally price accrual‐related information and that investors are functionally fixated. This study documents the importance of performing robustness tests when testing economic or behavioral explanations for apparent accounting‐related security mispricing. We find that performing robustness tests that exclude a small number of firm‐year observations (approximately 200 firm‐year observations or about 1% of the entire sample) reveals an inverted U‐shaped relation between buy‐and‐hold abnormal returns and total accruals. An inverted U‐shaped relation is inconsistent with the functional fixation (earnings fixation) hypothesis. We conduct similar robustness tests for the abnormal accrual anomaly and the net operating assets anomaly proposed by other investigators, and also find an inverted U‐shaped relation between buy‐and‐hold abnormal returns and abnormal accruals and net operating assets. These findings are inconsistent with the explanations put forth by those investigators. Such evidence leads us to conclude that the accrual‐related anomalies are unlikely to be due to investors' inability to process accounting information, as suggested by the functional fixation hypotheses tested.